2015
DOI: 10.3917/rfs.563.0439
|View full text |Cite
|
Sign up to set email alerts
|

Comment les firmes se financiarisent : le rôle de la réglementation et des instruments de gestion.

Abstract: L’étude de la mise en œuvre, dans une petite banque mutualiste, des Accords de « Bâle II » permet de documenter certains processus de financiarisation des entreprises. Ces derniers ne passent pas nécessairement par l’entrée dans le capital des entreprises d’investisseurs institutionnels orientés vers la création de valeur pour l’actionnaire. Dans le cas étudié, ce sont les choix réglementaires faits tant par l’Union européenne que par le superviseur bancaire français qui ont conduit cette banque à transformer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
0
2
0
12
Order By: Relevance
“…Pour ce faire, ces dernières ont transformé leur modèle de fonctionnement et notamment leurs systèmes de production et d'organisation. Elles ont intégré des outils de contrôle et de reporting sophistiqués (Baud & Chiapello, 2015) pour garantir un profit maximum à toutes les étapes de la production. Et même si l'empreinte de la financiarisation n'est pas toujours facile à identifier (Chambost, Tadjeddine, & Vincensini, 2018), il n'en reste pas moins que de nombreux travaux convergents pour dire que les processus de financiarisation sont très probablement la cause d'un dérèglement de l'économie et de dysfonctionnements des entreprises.…”
Section: Financiarisationunclassified
“…Pour ce faire, ces dernières ont transformé leur modèle de fonctionnement et notamment leurs systèmes de production et d'organisation. Elles ont intégré des outils de contrôle et de reporting sophistiqués (Baud & Chiapello, 2015) pour garantir un profit maximum à toutes les étapes de la production. Et même si l'empreinte de la financiarisation n'est pas toujours facile à identifier (Chambost, Tadjeddine, & Vincensini, 2018), il n'en reste pas moins que de nombreux travaux convergents pour dire que les processus de financiarisation sont très probablement la cause d'un dérèglement de l'économie et de dysfonctionnements des entreprises.…”
Section: Financiarisationunclassified
“…A relationship has indeed been established by studies interested in how regulatory frameworks align the organization and the strategies of non-financial firms on those of the financial sector. Baud and Chiapello (2015), in particular, have shown that managerial tools and practices imposed by the Basel agreements (largely informed by financial theory) were instrumental in the financialization of small and non-profit banks organized around different principles – leading to a rapid conversion of these firms. This indicates that the financialization of PHI could be a result of firms gradually adopting the routines, strategies and positioning of financial companies as they implement the regulatory provisions entrenched by Solvency II.…”
Section: Financialization Regulation and European Private Health Insu...mentioning
confidence: 99%
“…While the directors of real estate companies adopted financial reasoning and instruments from the outset, it was to be expected that the principle of 'colonization' would be evidenced in the gradual spread of financial reasoning to the lower levels of real estate organizations (see Baud and Chiapello, 2015). Real estate developers, in particular, increasingly come into contact with financial investors as shareholders in their firms (Romainville, 2017;Shimbo, 2019) or as representatives of real estate investment trusts (called 'fonci eres' in French).…”
Section: The Work Of Middle Management Far Away From Financial Toolsmentioning
confidence: 99%